Audio Bio Harmonic with WT5001 Smartchipusing Solar Cell: Nur Kadarisman, Fitria Ayu Sulistiani, Wipsar Sunu Brams Dwandaru, Rhyko Irawan Wisnuwijaya, Agus Sugiarto - Nur Kadarisman Nur Kadarisman; Fitria Ayu Sulistiani Fitria Ayu Sulistiani; Wipsar Sunu Brams Dwandaru Wipsar Sunu Brams Dwandaru; Rhyko Irawan Wisnuwijaya Rhyko Irawan Wisnuwijaya; Agus Sugiarto Agus Sugiarto (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2020)
The design of audio bio harmonic (ABH) with smartchip WT5001 using solar cell technology in the form of ABH instrumentation with an electricity resource derived from solar energy has been successfully created and tested, which includes (i) testing the peak frequency of sound and sound output, and (ii) emptying and charging tests to determine the effectiveness of the use of the solar cell as the power provider. The ABH system consists of (i) a sound generator device composed of WT5001 sound modules, amplifiers, and horn speakers, and (ii) structured power supply devices for solar cell modules, charger controllers, and batteries for storing power. The test results of the peak frequency for the insect (garengpung) sound files and the output sound of the ABH device indicate a deviation of peak frequency of 13.46 Hz to140.81 Hz. The 15 hours emptying test results in on mode with battery charging for 7 hours shows that the use of 10Wp solar cell is effective to provide electrical power in ABH tool operation.